COGNITIVE SKILLS OF STUDENTS IN MOTHER TONGUE LESSONS DEVELOPMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article offers innovative technologies in the study of cognitive skills, as well as considers the problems of forming students ' communicative competence.